Language Politeness in Tere Liye's Novel “Leaves That Feel Never Hate the Wind” Deixis Study - M. Joharis Lubis; Fitri Noviyanti Nasution (Britain International for Academic Research (BIAR-Publisher), 2021)
The purpose of this study was to determine the politeness of language in Tere Liye's novel